Overexpression of Yes‐associated protein and its association with clinicopathological features of hepatocellular carcinoma: A meta‐analysis. (24th April 2017) - Lin, Chengjie; Hu, Zhigao; Lei, Biao; Tang, Bo; Yu, Hongping; Qiu, Xiaoqiang; He, Songqing
Abstract: Background: Yes‐associated protein (YAP) overexpression is reported to be associated with risk of hepatocellular carcinoma (HCC) but current studies have not explored the relationship between YAP expression with HCC clinicopathological features. Methods: To assess these associations, a meta‐analysis was performed which included four eligible studies including 391 HCC cases and 334 controls. There were eight eligible studies to investigate the association between YAP expression in HCC and clinicopathological features of liver cancer patients. Literature was obtained from PubMed, Embase, Wangfang and China National Knowledge Infrastructure. Results: Analysis indicated that YAP expression in HCC was greater than in adjacent non‐tumour tissue (odds ratio [OR], 15.80, 95% confidence interval [CI], 10.53‐23.70, P <.00001; heterogeneity=.30). YAP overexpression in HCC was significantly associated with vascular invasion (OR, 2.21, 95% CI, 11.64‐2.97, P <.00001, heterogeneity=.10), less cellular differentiation (OR, 2.38, 95% CI, 1.61‐3.51, P <.00001, heterogeneity=.333), tumours larger than 5 cm (OR, 2.52, 95% CI, 1.75‐3.62, P <.00001; heterogeneity=.17) and TNM tumour stage I + II (OR, 0.44, 95% CI, 0.28‐0.75, P =.00003, heterogeneity=.12). Conclusions: Overexpression of YAP contributes to HCC formation, and its overexpression is associated with vascular invasion, low cellular differentiation tumours larger than 5 cm and TNM tumour stage III + IV.